Pelatihan Pemanfaatan Limbah Kain Perca menjadi Scrunchie untuk Meningkatkan Kreativitas dan Nilai Ekonomi Produk - Inda Arfa Syera; Dewi Hakiki; Windi Triana; Rahmat Suhargon (Community Service Progress, 2026)
Fabric scraps are a type of textile waste whose volume continues to increase along with the development of the fashion industry and the garment industry. The utilization of fabric scraps into useful and economically valuable products is still not optimal, including among students who have entrepreneurial knowledge but lack the practical skills to produce business products. This community service activity aims to improve students' creativity and entrepreneurial skills through training in utilizing fabric scraps into scrunchies. The activity was held on May 12, 2026, in the Muhammadiyah Asahan University Hall, involving 44 members of the Entrepreneurship UKM consisting of students from the Management Study Program and the Accounting Study Program. The methods used included socialization, demonstrations, direct practice, and evaluation. The results of the activity showed that the participants had high enthusiasm during the training. All participants were able to follow the scrunchie-making process and successfully produced products independently from the provided fabric scraps. In addition to improving technical skills in product manufacturing, the training also increased participants' understanding of textile waste management and business opportunities that can be developed from recycled products. The resulting scrunchie products have utility value, aesthetic value, and economic potential, making them an alternative for environmentally-based creative businesses. This activity successfully increased students' creativity and entrepreneurial skills while supporting efforts to reduce textile waste by reusing leftover materials into more valuable products.